Interações sociais de casais vivendo com HIV dez anos após introdução dos anti-retrovirais no Brasil - Juliana Mara Felisberto (2009)
This study has the objective to comprehend the social interactions of couples affected by the HIV ten years after the institution of the anti-retroviral therapy (ARVT), comparing its results with the study done by Freitas, in 1998, about the same object and using the same methodology. The theoretical-methodological proposal, with a qualitative aspect, is funded on the interaction theories and was done with open interviews, analyzed based on the structural narration analysis. Six heterosexual couples, with at least one year of common life and being treated for HIV/aids in a public service in the city of Belo Horizonte, Brazil were interviewed. The data interpretation pointed three thematic categories: The discovery of the soropositivity by the partners; The interaction in the inside of the couple; The interaction of the couple with the exterior. In the moment of the discovery, there is still presence of fear of the unexpected, shock, sadness, apprehensiveness and get away, even though the participants knew the scientific advances in the HIV field. The current speeches show a smaller fear of death, intensely present ten years ago, but this fear is implied when people affirm the need to change the view of life to do short terms plans. The relationship was approached by the participants before the diagnosis, during the revelations and how it is today. The difficulties are the same and the various forms of secrets travel between the confidence and the lack of confidence in the daily life of the couple. When it comes to family, there are choices to reveal or hide the truth about the diagnosis, existing the need of dissimulations, small lies and omissions, generally to protect the risk of prejudice or to protect the family members from suffering. In the interactions with the social circle, the couples continue to maintain the secret about the seropositivity, especially because of prejudice. Only the closer ones share the diagnosis, and there are no changes related to the results found in the study of 1998. There are difficulties to socialize and adapt to the new life path and the health professionals must create accompaniment strategies that include the care for the couples and for their families.